1993
DOI: 10.2307/3578875
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Evaluation of Radiation-Induced Glomerular Ultrastructural Changes in the Pig Kidney

Abstract: Both kidneys of 12 mature female pigs received either a single dose of 9.8 Gy 60Co gamma rays or sham irradiation. At intervals of 1-4 weeks serial renal biopsies were obtained, followed by sacrifice at 24 weeks after irradiation. Individual kidney glomerular filtration rate (GFR), effective renal plasma flow (ERPF), and the hematocrit (Hct) were measured routinely. Renal irradiation resulted in a progressive decline in GFR, ERPF, and Hct, with minimal values being observed within 12 weeks of irradiation. No c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…One of the morphologic changes that endothelial cells are reported to undergo in vivo, after irradiation, is swelling. 3,33 It is conceivable that the upregulated levels of CD31 on irradiated HUVECs may have been due to an increase in cell surface area. However, the data from the flow cytometric analysis of forward scatter, which is proportional to cell size, showed that the increase in CD31 far exceeded any alterations in size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the morphologic changes that endothelial cells are reported to undergo in vivo, after irradiation, is swelling. 3,33 It is conceivable that the upregulated levels of CD31 on irradiated HUVECs may have been due to an increase in cell surface area. However, the data from the flow cytometric analysis of forward scatter, which is proportional to cell size, showed that the increase in CD31 far exceeded any alterations in size.…”
Section: Discussionmentioning
confidence: 99%
“…1 The blood vessels in irradiated normal tissues often undergo adverse changes that can compromise their functions, and because these changes precede the development of fibrosis, it has been hypothesized that vascular damage could be an important factor in the pathogenesis of late radiation damage. 2 Endothelial cell dysfunction after irradiation can be recognized by morphological changes such as cell swelling, 3 increased leukocyte-endothelial cell adherence and infiltration of leukocytes into tissues, [2][3][4][5][6] platelet adherence to the vascular wall, 7 a loss in vascular wall integrity resulting from reduced endothelial cell numbers, and the formation of tortuous vessels. 8 Recent experimental evidence suggests that radiation-induced expression of the membrane glycoproteins E-selectin and intercellular adhesion molecule 1 (ICAM-1) on endothelial cells is involved in the mechanisms mediating increased leukocyte-endothelial cell interactions after irradiation.…”
mentioning
confidence: 99%
“…Leukocyte infiltration and accumulation in irradiated pig kidney and rat rectum have been well documented 4,5) . However, the pathological consequences of leukocyte infiltration and accumulation in irradiated normal tissues are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Systolic blood pressure 46 , blood urea nitrogen (BUN; an excellent surrogate marker for renal injury), serum creatine and clearance, glomerular filtration rate (GFR) 47 and urine protein are some of important functional end points which have been used widely for evaluating agents for their efficacy. Rat (out-bred CD(SD), WAG/Rij) is more reliable model for radiation-induced kidney damage as mouse exhibit radioresistance.…”
Section: Kidneymentioning
confidence: 99%